2017
DOI: 10.1021/acs.est.7b00933
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Risks from Agricultural Pesticides in Small Streams

Abstract: Small streams are important refuges for biodiversity. In agricultural areas, they may be at risk from pesticide pollution. However, most related studies have been limited to a few streams on the regional level, hampering extrapolation to larger scales. We quantified risks as exceedances of regulatory acceptable concentrations (RACs) and used German monitoring data to quantify the drivers thereof and to assess current risks in small streams on a large scale. The data set was comprised of 1 766 104 measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 44 publications
(102 reference statements)
4
65
1
2
Order By: Relevance
“…The investigation of large-scale risks from agricultural pesticides in small streams in Germany shows a positive relationship between agricultural land use and the number of regulatory acceptable concentration (RAC) exceedances. [3] The catchment size had no statistically significant effect on the number of RAC exceedances, however previous studies showed that small streams are more polluted than bigger streams. [88][89][90] Additionally, precipitation before sampling had a stronger effect than during sampling on the probability of exceeding LOQ.…”
Section: Neonicotinoidsmentioning
confidence: 79%
See 2 more Smart Citations
“…The investigation of large-scale risks from agricultural pesticides in small streams in Germany shows a positive relationship between agricultural land use and the number of regulatory acceptable concentration (RAC) exceedances. [3] The catchment size had no statistically significant effect on the number of RAC exceedances, however previous studies showed that small streams are more polluted than bigger streams. [88][89][90] Additionally, precipitation before sampling had a stronger effect than during sampling on the probability of exceeding LOQ.…”
Section: Neonicotinoidsmentioning
confidence: 79%
“…Additionally, precipitation before sampling had a stronger effect than during sampling on the probability of exceeding LOQ. Among the fifteen compounds with the highest observed RQ in small streams, thiacloprid, imidacloprid, and clothianidin had the highest values …”
Section: Occurrence Of Pesticides In Water In the Eu And Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…Ecoregions are distinct geospatial units that represent unique patterns of environmental and ecological variables. As such, ecoregions are considered particularly useful for risk assessment and conservation planning at a larger scale (Schäfer et al 2013, Szöcs et al 2017. The AR for each freshwater ecoregion b (AR b ) was calculated as the average risk-quotient over its total water volume (equation (5)).…”
Section: Aquatic Risks (Ars)mentioning
confidence: 99%
“…Pesticides runoff to surface water poses a risk to the aquatic environment, and recent studies show that pesticides from agricultural land use are a major threat to small streams and their biodiversity [1] [2].…”
Section: Introductionmentioning
confidence: 99%